Does innovation policy drive rural revitalization in China? - An empirical study based on Chinese rural areas - Zhige Ying; Cheng Zhang; Hande Chen; Zhiyuan Cheng; Zhe Wu (PLoS ONE, 2025)
Innovation serves not only as the cornerstone of rural revitalization but also as the fundamental driving force behind agricultural and rural modernization in China. Since 2008, China has initiated the implementation of innovative city pilot projects, gradually expanding their scope. This study, based on mechanism analysis, employs panel data from 280 cities and local rural areas spanning from 2004 to 2018 to empirically examine the impact of pilot policies on local rural revitalization levels using methods such as the difference-in-differences model. The research findings indicate that innovative city pilot policies significantly enhance rural revitalization levels. Heterogeneity analysis reveals that the effect of innovation policies is pronounced in cities with high entrepreneurial activity but shows no significant correlation with city level, or science and education resources. Furthermore, the study finds that innovative city pilot policies contribute to strengthening local rural communication levels, cultural and educational development, promoting talent aggregation, and indirectly facilitating other policies supporting rural areas, thereby positively influencing rural development. Additionally, the aggregation effect of talents and the incentive effect on business investment are crucial reasons for enhancing urban innovation levels. The conclusions drawn in this study provide policy insights for fully unleashing the rural revitalization effects of innovation-driven policies, thus promoting high-quality economic development in China and enhancing the international community’s understanding of Chinese policies and rural areas.